The Effect Of Carbon Monoxide Gas Exposure Levels On Oxygen Saturation In Parking Attendants - Dewi Lia Listyawati; Rachmaniyah; Marlik; Khambali; Edza Aria Wikurendra (Window of Health : Jurnal Kesehatan, 2024)
Parking attendants are susceptible to health problems due to their ongoing exposure to vehicle-related air pollution. A significant contaminant called carbon monoxide (CO) binds to hemoglobin 200 times more strongly than oxygen, forming carboxyhemoglobin (COHb) and causing a decrease in blood oxygen saturation. This study aims to investigate how CO exposure affects the oxygen saturation levels of parking attendants at Surabaya's Kapasan Market. The study uses a cross-sectional methodology and quantitative analysis. Thirteen people made up the study's sample size, including all parking attendants at Kapasan Market in Surabaya. The concentration of CO gas, the workday length, and the oxygen saturation levels were the variables examined. The Spearman's rank correlation test was used to examine the data. The average CO gas level was 3.53 PPM, the average workday for the attendants was 7.5 hours, and the average oxygen saturation was 95%, according to the findings. CO levels and oxygen saturation showed a strong correlation (p = 0.010), as did work time and oxygen saturation (p = 0.005). It is advised that parking attendants take frequent breaks from their duties to breathe in fresh air, take vitamins and supplements, eat a healthy diet, and engage in little physical activity.